2018
DOI: 10.1136/bmjoq-2017-000200
|View full text |Cite
|
Sign up to set email alerts
|

TIME to think about delirium: improving detection and management on the acute medical unit

Abstract: Delirium affects 18%–35% patients in the acute hospital setting, yet is often neither detected nor managed appropriately. It is associated with increased risk of falls, longer hospital stay and increased morbidity and mortality rates. It is a frightening and unpleasant experience for both patients and their families. We used quality improvement tools and a multicomponent intervention to promote detection and improve management of delirium on the acute medical unit (AMU). We reviewed whether a delirium screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…However, there is growing interest in quality improvement approaches, which seem to show promise. For example, a combination of staff education and use of the Think, Investigate, Manage, Engage (TIME) bundle 241 , which targets delirium treatment actions in the first 2 hours following diagnosis, led to improvements in the assessment of delirium causes and exacerbating factors 272 . Furthermore, educational interventions can lead to improvements in the process of care; a systematic review of 42 studies involving educational interventions found that 90% of these studies demonstrated a beneficial effect on one or more measures, some of which were related to the delivery of delirium treatment 273 .…”
Section: Multidomain Treatment Of Deliriummentioning
confidence: 99%
“…However, there is growing interest in quality improvement approaches, which seem to show promise. For example, a combination of staff education and use of the Think, Investigate, Manage, Engage (TIME) bundle 241 , which targets delirium treatment actions in the first 2 hours following diagnosis, led to improvements in the assessment of delirium causes and exacerbating factors 272 . Furthermore, educational interventions can lead to improvements in the process of care; a systematic review of 42 studies involving educational interventions found that 90% of these studies demonstrated a beneficial effect on one or more measures, some of which were related to the delivery of delirium treatment 273 .…”
Section: Multidomain Treatment Of Deliriummentioning
confidence: 99%
“…We suggest that in an acute hospital environment, a positive 4AT highlights patients at increased risk of adverse outcome. We recommend pairing of a comprehensive delirium management strategy (such as the TIME Bundle from the Scottish Delirium Association) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies aimed at improving the use of 4AT screening have shown a 21-64% improvement of screenings (45)(46)(47)(48). However, Bearn et al (47) was the only study with a baseline screening of 0%, as in our study, implying that the 4AT instrument was already known and in use by the healthcare staff in the other studies.…”
Section: Detection and Screening Of Cognitive Impairmentmentioning
confidence: 43%